Pelvic tilt impacts cup orientation on CT: how accurate is the gold standard?. (May 2022) - Kaiser, Moritz; Renkawitz, Tobias; Benditz, Achim; König, Matthias; Thieme, Max; Weber, Markus
Background: Computed tomography (CT) is the gold standard for the accurate measurement of cup inclination and anteversion in total hip arthroplasty (THA). However, functional cup position strongly depends on the tilt of the pelvis and thus pelvic tilt in the supine position on the CT table harbors the risk of misinterpretation. Purpose: To evaluate the influence of pelvic tilt on cup measurements in postoperative CT scans. Material and Methods: This is a secondary outcome analysis of a prospective study. In 123 patients undergoing THA, anatomic cup inclination and anteversion as measured on postoperative 3D-CT scans were compared between: (i) the anterior pelvic plane (APP) resembling neutral pelvic tilt; and (ii) the coronal plane representing the standard planes on CT. Furthermore, the effect of the variation on cup positions within Lewinnek's safe zone in relation to the applied reference plane was assessed. Results: Mean pelvic tilt in supine position was –3.5° ± 5.6°. This resulted in a mean difference for anteversion between APP und coronal plane of 2.1° ± 3.7° and of 2.1° ± 1.9° for cup inclination, respectively. The change varied up to 20.2° for cup inclination and up 12.2° for cup anteversion. The overall conversion rate for inclination and/or anteversion regarding Lewinnek's safe zone was high at 23.6% (29/123). Conclusion: Pelvic tilt affects cup orientation on CT scans depending on the applied reference plane. Standard CT planes should be corrected regarding pelvic tilt before measurements to avoid errors in measurement.